Nutrition-related diseases and cardiovascular mortality in American society: national health and nutrition examination study, 1999-2006 - Weihua Chen; Shanshan Shi; Jiabin Tu; Lihua Liao; Ying Liao; Kaihong Chen; Liling Chen; Rongchong Huang (BMC, 2022)
Abstract Background Despite many significant advances in treatment and management, cardiovascular disease remains the main cause of the global disease burden. Nutrition-related disease is a modifiable cardiovascular risk factor. However, few studies have examined the relationship between nutrition-related diseases and cardiovascular mortality. Objective We aimed to investigate the association of nutrition-related diseases with cardiovascular mortality based on a large nationally representative community population. Design We analyzed data from the National Health and Nutrition Examination Survey (NHANES) 1999-2006 with mortality follow-up through December 31, 2015. Finally, 12,469 participants were analyzed. Each participant was assigned to one of four groups: normal nutrition without sarcopenia, sarcopenia with normal nutrition, malnutrition without sarcopenia, and malnutrition-sarcopenia syndrome. Survival curves and Cox regressions based on the NHANES recommended weights were used to assess the association between nutrition-related diseases and cardiovascular mortality. Results Of the 12,469 patients included in the study and divided into four groups, malnutrition-sarcopenia syndrome had the highest 5- and 10-year cardiovascular mortality rates. After adjustment for related factors, sarcopenia with normal nutrition (hazard ratio [HR]: 1.62, 95% confidence interval [CI]: 1.28-2.06; P < 0.001), malnutrition without sarcopenia (HR: 1.28, 95% CI:1.03-1.58; P = 0.024), and malnutrition-sarcopenia syndrome (HR: 2.66, 95% CI:1.89 − 3.74; P < 0.001) were significantly associated with increased risk of all-cause mortality. Malnutrition-sarcopenia syndrome remained associated with an increased risk of cardiovascular mortality (HR: 3.56, 95% CI: 1.17 − 10.84; P < 0.001). Conclusions Malnutrition-sarcopenia syndrome was highly prevalent among community-dwelling adults in the United States and was a strong prognostic factor for cardiovascular mortality in the community setting. Randomized clinical trials are needed to demonstrate whether prevention or treatment of malnutrition-sarcopenia syndrome in community populations can reduce global cardiovascular mortality.